Benefit-sharing arrangements between oil companies and indigenous people in Russian northern regions - Tulaeva, Svetlana; Tysiachniouk, Maria (Sustainability, 2017)
This research provides an insight into various modes of benefit-sharing agreements between oil and gas companies and indigenous people in Russia’s northern regions, e.g., paternalism, corporate social responsibility, and partnership. The paper examines factors that influence benefit-sharing arrangements, such as regional specifics, dependency on international investors, corporate policies, and the level of local community organization. It analyses which instruments of benefit-sharing are most favourable, and why, for indigenous communities. The authors conducted research in three regions of Russia (Nenets Autonomous Okrug; Khanty-Mansi Autonomous Okrug, and Sakhalin) by using qualitative methodology that involved semi-structured interviews, participant observation, and document analysis. Theoretically, the paper builds on the concept of benefit-sharing arrangements combined with the social equity framework. We assessed each case study in terms of procedural and distributive equity in benefit-sharing. The paper demonstrates that the procedural equity is the highest in the partnership mode of benefit-sharing on the island of Sakhalin where companies implement globally-accepted standards recognized by investment banks. The cases in Nenets Autonomous Okrug and Khanti Mansi Autonomous Okrug represent a reset of Soviet practices on a market basis, but whereas the distributional equity may be sufficient, the procedural equity is low as decisions are made by the company in concord with regional authorities.